Lysophosphatidic acid induces glycodelin gene expression in cancer cells - Ramachandran, Sumathi; Ramaswamy, Sreemathy; Cho, Chi-heum; Parthasarathy, Sampath (Cancer letters, 2002)
Glycodelin is a glycoprotein that has been suggested to be important in normal pregnancy and in malignancy. The regulation of its synthesis has not been studied. In this study, we report the induction of glycodelin gene expression by lysophosphatidic acid (LPA). We studied the effect of LPA (5, 10 and 25 μM) on glycodelin production in breast (MDA-MB-231), cervical (Hela), endometrial (RL-95), ovarian cancer (OVCAR-3) and erythroleukemia (K562) cells. There was a dose-dependent (5–25 μM) induction of glycodelin gene and protein expression in these cell types. LPA is a mimic of phorbol myristate acetate (PMA) action and is found to be elevated in high concentrations in the serum of cancer subjects. As glycodelin is an angiogenic protein with a potential immunosuppressive role, control of LPA synthesis might offer a potential target for intervention.